Cytokines Play a Key Role in Communication between Mesenchymal Stem Cells and Brain Cancer Cells - Motaln, Helena; Lah Turnsek, Tamara (Protein and Peptide Letters, 2015)
Numerous small molecules including cytokines primarily associated with immune response have been shown to play a role in normal mesenchymal stem cells (MSC) and tumour cells’ communication. One characteristic that distinguishes MSC from fibroblast and other cells of mesenchymal origin is their pro-tumour migratory behaviour. Recognizing the cytokines as key players of the MSC/tumour cell cross-talk and understanding their intracellular signalling, should lead to a development of more efficient anti-tumour therapies. Those are urgently needed for improving the treatment of patients with glioblastoma multiformae (GBM) that are suffering from most aggressive and incurable type of brain tumours. So far, the “cytokine signalling interference” approach, employing genetically modified MSCs and GBM cells in animal xenograft models pointed to the mechanisms underlying tumour - directed migration and immunomodulatory role of MSCs. There, MSC’s effects on tumour growth were shown to vary substantially, and to depend on the type of the cells and the animal model used. This review is focusing on the cytokines produced by MSCs and their involvement in proliferation, migration, angiogenesis, apoptosis and immune cell infiltration. Recently, targeted therapies have emerged as a promising modality for GBM treatment. New approaches, combining these with MSCs as cellular vectors for modulating cytokines and cytokine receptors’ signalling in GBM may thus prove more efficient at inhibiting glioma progression.
Keywords: immunomodulation